The Effectiveness of Cognitive Behavioral Therapy on Emotion Regulation and Problem-Solving in Adolescents - Kazemi , Reza; Hoseyni, Seyyed Zohre (Mental Health and Lifestyle Journal, 2024)
The aim of the present study was to determine the effectiveness of Cognitive Behavioral Therapy (CBT) on emotion regulation and problem-solving in adolescents. The research method was quasi-experimental with a pretest-posttest control group design. The statistical population consisted of adolescents who referred to counseling centers in Rasht during the second half of the year 2023. Using convenience sampling, 30 individuals were selected and randomly assigned to experimental and control groups. The data collection instrument included the Emotion Regulation Questionnaire. Participants in the experimental group received CBT sessions for eight consecutive weeks, with one 90-minute session per week. No intervention was provided to the control group. The findings indicated that the mean score of emotion regulation in the posttest was significantly higher than in the pretest for the experimental group. Therefore, it can be concluded that Cognitive Behavioral Therapy is effective in enhancing emotion regulation and problem-solving among adolescents.